Childhood Traumatic Experiences and Trauma Related Psychiatric Comorbidities in Dissociative Disorders - YANARTAŞ, ÖMER (KURE ILETISIM GRUBU A S, 2015)
Objective: Different prevalence rates are reported for dissociative disorders (DD) in different clinical populations (inpatient, outpatient, emergency). It is around 10% among admissions to psychiatry outpatient clinics. Since DD harbors disruption/discontinuation of memory, identity, emotion, and perception many other psychiatric symptoms may be triggered by it. On the other hand, high amount of childhood traumatic experiences in DD patients may be associated with comorbid trauma related psychiatric disorders among them. We aimed to determine the diagnostic distribution of DD in psychiatric outpatients; to show the types of childhood traumatic experiences, their frequencies and sub-types, and co-morbid psychiatric disorders related to these traumas; and to compare the patients with and without DD diagnoses. Methods: We conducted a cross-sectional study involving 1314 participants who were screened with the Dissociative Experience Scale (DES) and the Somatoform Dissociation Questionnaire (SDQ). Of the participants, 272 who scored above the cut-off point of either of these scales (DES score > 30 or SDQ score >40 points) were invited to complete a structured interview using the Dissociative Disorders Interview Schedule (DDIS). Of this subsample, only 190 participants agreed to participate in this second phase of the study. A semi-structured interview form was applied to them to collect demographical and clinical variables. In these patients psychiatric comorbidity and trauma history were assessed according to DDIS sub-items, conversion disorder was diagnosed according to DSM IV-TR criteria, and post-traumatic stress disorder was diagnosed according to the post-traumatic stress disorder module of Structured Clinical Interview (SCID-I). Patients with DD diagnosis and without it were compared in terms of study variables. Results: In the first phase of the study, a total of 272 patients (20.7%) have scored above cut-off level of either of DES or SDQ. Of the 190 participants who were enrolled to the second phase, 167 patients were diagnosed with a dissociative disorder (87.8%). We found that dissociative disorder not otherwise specified was the most prevalent type of DD in these patients. All the measured traumatic experiences were significantly higher in the patients with DD than patients without DD, except for sexual abuse. When compared to patients with and without DD, borderline personality disorder, conversion disorder and lifetime major depressive episodes were significantly higher in the patients with DD (p=0.011, p=0.035, p=0.013, respectively). In the logistic regression analysis the neglect, physical trauma, verbal abuse/threat histories in childhood were identified as predictive factors of DD diagnosis (Table 5). Conclusion: Clinicians should keep in mind that around one fifth of psychiatry outpatients have clinically significant amount of dissociative symptoms. Childhood traumas and related psychiatric comorbidities are quite common among them with a higher frequency observed in those patients with DD diagnosis. Further studies are needed to determine dissociative symptoms, childhood trauma and trauma related psychiatric comorbidity of psychiatry outpatients and to understand better how they interact with each other especially in those diagnosed with DD.
Keywords: dissociative disorders; frequency; outpatients clinic; childhood trauma; trauma related comorbidity; BORDERLINE PERSONALITY-DISORDER; CONVERSION DISORDER; STRUCTURED INTERVIEW; IDENTITY DISORDER; SEXUAL ABUSE; INPATIENTS; FREQUENCY; PSYCHOPATHOLOGY; OUTPATIENTS; PREVALENCE